Visual Experiences during Paralysis - Whitham, Emma M.; Fitzgibbon, Sean P.; Lewis, Trent W.; Pope, Kenneth J.; DeLosAngeles, Dylan; Clark, C. R.; Lillie, Peter; Hardy, Andrew; Gandevia, Simon C.; Willoughby, John O. (Frontiers in Human Neuroscience, 2011)
Rationale: Paralyzed human volunteers (n = 6) participated in several studies the primary one of which required full neuromuscular paralysis while awake. After the primary experiment, while still paralyzed and awake, subjects undertook studies of humor and of attempted eye-movement. The attempted eye-movements tested a central, intentional component to one’s internal visual model and are the subject of this report. Methods: Subjects reclined in a supportive chair and were ventilated after paralysis (cisatracurium, 20 mg intravenously). In illumination, subjects were requested to focus alternately on the faces of investigators standing on the left and the right within peripheral vision. In darkness, subjects were instructed to look away from a point source of light. Subjects were to report their experiences after reversal of paralysis. Results: During attempted eye-movement in illumination, one subject had an illusion of environmental movement but four subjects perceived faces as clearly as if they were in central vision. In darkness, four subjects reported movement of the target light in the direction of attempted eye-movements and three could control the movement of the light at will. Conclusion: The hypothesis that internal visual models receive intended ocular-movement-information directly from oculomotor centers is strengthened by this evidence.